Blister Beetles (Insecta: Coleoptera: Meloidae) - Richard B. Selander; Thomas R. Fasulo (EDIS, 2004)
The family Meloidae, blister beetles, contains about 2500 species, divided among 80 genera and three subfamilies. Florida has 26 species, only a small fraction of the total number in the U.S., but nearly three times that in the West Indies (Selander and Bouseman 1960). Adult beetles are phytophagous, feeding especially on plants in the families Amaranthaceae, Compositae, Leguminosae, and Solanaceae. Most adults eat only floral parts, but some, particularly those of Epicauta spp., eat leaves as well. This document is EENY-166 (originally published as DPI Entomology Circular 268), one of the Featured Creatures series of the Entomology and Nematology Department, Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: October 2000. Revised: August 2003.